2021
DOI: 10.1515/jall-2021-2016
|View full text |Cite
|
Sign up to set email alerts
|

Documenting the Ikpana interrogative system

Abstract: This article provides a comprehensive treatment of the interrogative system of Ikpana (ISO 639-3: lgq), an endangered language spoken in the southeastern part of Ghana’s Volta region. The article features a description and analysis of both the morphosyntax and intonation of questions in the language. Polar questions in Ikpana are associated with dedicated prosodic patterns and may be segmentally marked. As for wh- interrogatives, Ikpana allows for optional wh- movement. Interrogative expressions may appear cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recent work on African languages, however, shows that numerous languages do not fit neatly within the traditional categories of islandhood (c.f. Wolof: Torrence 2005Torrence , 2012; Krachi: Torrence and Kandybowicz 2015; Asante Twi: Hein and Georgi 2020; Igbo: Georgi and Amaechi 2020; Shupamem: Schurr et al 2024; Akan: Murphy and Korsah, forthcoming; and Ikpana: Kandybowicz et al 2021Kandybowicz et al , 2023. In this paper, I show that islandhood in Mende, an understudied OV Mande language spoken in Sierra Leone, challenges the current theory.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Recent work on African languages, however, shows that numerous languages do not fit neatly within the traditional categories of islandhood (c.f. Wolof: Torrence 2005Torrence , 2012; Krachi: Torrence and Kandybowicz 2015; Asante Twi: Hein and Georgi 2020; Igbo: Georgi and Amaechi 2020; Shupamem: Schurr et al 2024; Akan: Murphy and Korsah, forthcoming; and Ikpana: Kandybowicz et al 2021Kandybowicz et al , 2023. In this paper, I show that islandhood in Mende, an understudied OV Mande language spoken in Sierra Leone, challenges the current theory.…”
Section: Introductionmentioning
confidence: 69%
“…The re ative clause raises first into SpecExtraP before the DP head of the clause remnant mov into its higher position. I have shown that while wh-movement is possible out of a subjec Extraction out of relative clauses has been indicated in the literature, particularly in African (Kandybowicz et al 2021(Kandybowicz et al , 2023Schurr et al 2024;Murphy and Korsah, forthcoming) and Mainland Scandinavian languages (Engdahl 1997;Kush et al 2013Kush et al , 2019Müller 2014Müller , 2015. Studies indicate that there is an A-bar movement from relative clauses (Christensen and Nyvad 2014;Lindahl 2014Lindahl , 2017Lindahl , 2022, and there is consensus that relative clauses are weak islands in various languages, including Danish (Müller and Eggers 2022) and Swedish (Lindahl 2014), as well as English (Vincent et al 2022) and Hebrew (Sichel 2018).…”
Section: Object-modifying Configurationmentioning
confidence: 77%
See 1 more Smart Citation